Characterisation of actinobacteria isolated from Padina Ap. And intertidal sediments of Tanjung Tuan, Malaysia / Teo Wee Fei Aaron - Teo, Wee Fei Aaron (2014)

(untitled)
Microbial populations in human inhabited coastal environment are subject to disturbance and human activity. Thus, the diversity of microbes in this environment is often interesting because of the challenges that the microbial population faced. In this study, actinobacteria was isolated from intertidal sediment samples and Padina antillarum (Dictyotales, Phaeophyceae) from Tanjung Tuan (Cape Rachado), Port Dickson, Malaysia. Isolates were subjected to polymerase chain reaction (PCR) screening specific for Streptomycetaceae and Micromonosporaceae, prior to characterization by phenotypic characterisation and its genotyping for the purpose of clustering. Molecular identification by 16S rRNA gene sequence revealed five families and nine genera, namely Streptomycetaceae, Micromonosporaceae, Pseudonocardiaceae, Nocardiaceae and Tsukamurellaceae. The presence of a relatively higher number of isolates belonging to Streptomycetaceae and Micromonosporaceae is as expected. However, two endophytic isolates PE32 and PE37 have been identified to be closely related to the clinical actinobacteria Nocardia nova (99.9% pairwise similarity) and Williamsia muralis (99.4% pairwise similarity), respectively. Isolate PE36 could be a novel species within the genus Prauserella, with 96.6% pairwise similarity to the closest identification, Prauserella marina. Additional characterization to identify potentially bioactive isolates were carried out to detect ketoacyl synthase and methyl- transferase domain of malonyl -type I polyketide synthases (PKSI) and adenylation domains in non- ribosomal peptide synthetase (NRPS) . Isolates were also evaluated for antibacterial activity against Escherichia coli, Staphylococcus aureus and Bacillus subtilis by resazurin based microtitre assay. The presence of the target genes and detectable antibacterial activity showed a high correlation. Additionally isolate SE31 was wholly genome sequenced.